Analisis Performa Website Perpustakaan Universitas Malikussaleh Menggunakan Metode Load Testing dengan Apache JMeter - Sahputra, Ilham (Universitas Multi Data Palembang, 2025)
The Universitas Malikussaleh library website plays a vital role in supporting academic activities for students and lecturers. System performance degradation during high traffic periods—such as exam weeks—can disrupt access to essential services. This study aims to evaluate the website’s performance through Load Testing using Apache JMeter. Three test scenarios were conducted under simulated loads of 100, 200, and 300 concurrent users, measuring key performance parameters including response time, throughput, and system stability. Results show that the website remained stable up to 200 users. However, under 300 users, performance significantly declined, marked by increased response times, reduced throughput, and bottlenecks on features like OPAC and online registration. These issues highlight limitations in the current infrastructure, particularly due to shared hosting. Based on the findings, several recommendations are proposed: upgrading server capacity, optimizing resource-intensive features, implementing caching mechanisms, and applying load balancing techniques. With these improvements, the library website is expected to deliver faster, more reliable services and be better equipped to handle traffic surges in the future